RANCANGAN ALTERNATIF PENGELOLAAN SAMPAH PLASTIK UNTUK TAMU HOTEL UPAYA MENDUKUNG PARIWISATA BAHARI BERKELANJUTAN (STUDI KASUS DI MONOLOOG HOTEL JAKARTA PASAR BARU - Soraya Fitriaputri Mirzadania (STAH Dharma Sentana Sulawesi Tengah, 2026)
Marine pollution is essentially caused by three main factors: pollution from land, pollution from marine sources or maritime activities, and pollution from air activities over the sea, originating from land or directly discharged from the shore, then carried by currents or winds, spreading to various coastal areas. Based on this research, the problem identification and the objective of this study are to design an e-pocketbook as an alternative guide for plastic waste management and to determine how the e-pocketbook design benefits guests at Monoloog Hotel Jakarta Pasar Baru. To gather data and information, this study was conducted from May 2024 to June 2024 at Monoloog Hotel Jakarta Pasar Baru. The research method approach uses a mixed-methods approach with data collection through observation, interviews, and questionnaires with a total of 100 respondents using the Likert scale analysis tool. Meanwhile, the prototype design method uses an appreciative methods. The prototype design results were tested through brief questions rated from 1 (not useful at all) to 5 (very useful) to assess its effectiveness. Based on the research results, the prototype design was deemed feasible by the hotel guests. Suggestions for future researchers are expected to realize the e-pocketbook by first evaluating it to meet the needs of Monoloog Hotel Jakarta Pasar Baru guests.